2011
DOI: 10.3354/meps09131
|View full text |Cite
|
Sign up to set email alerts
|

Small macrobenthic invertebrates affect the mortality and growth of early post-settlement sea urchins and sea stars in subtidal cobble habitat

Abstract: Early post-settlement events can have a large impact on the successful recruitment of benthic invertebrates. A field caging experiment was conducted in 2007 to examine whether predation by, and/or competition with, small macrofauna affects mortality or growth of recently settled sea urchins Strongylocentrotus droebachiensis or sea stars Asterias spp. Kelp was added to half of the sea urchin cages to test whether the addition of this food source (including its associated biofilms) altered growth or survival. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…This convincingly indicates the importance of metamorphosis in the formation of photosensory elements. Survival and growth of recently settled sea urchins would be significantly affected by the presence of predators (Scheibling & Robinson 2008;Jennings & Hunt 2011). Photosensory elements are probably essential for early post-settlement sea urchins to avoid predation and consequently to have a significant impact on their successful recruitment, although relevant experimental evidence is limited to adult urchins.…”
Section: Discussionmentioning
confidence: 99%
“…This convincingly indicates the importance of metamorphosis in the formation of photosensory elements. Survival and growth of recently settled sea urchins would be significantly affected by the presence of predators (Scheibling & Robinson 2008;Jennings & Hunt 2011). Photosensory elements are probably essential for early post-settlement sea urchins to avoid predation and consequently to have a significant impact on their successful recruitment, although relevant experimental evidence is limited to adult urchins.…”
Section: Discussionmentioning
confidence: 99%
“…Cannibalism by larger juvenile sea urchins was hypothesized to be a possible mechanism of mortality in a field experiment where 1 to 3 mm TD S. droebachiensis settlers were placed in cages along with the suite of organisms (chitons, scale worms and larger sea urchins) found on the cobble bottom surrounding the cages in the Passamaquoddy Bay, New Brunswick (Jennings & Hunt 2011). In cages with the suite of organisms, sea urchin mortality was 25% higher than in cages without the suite (Jennings & Hunt 2011, Jennings & Hunt 2014. A follow-up laboratory experiment by Jennings & Hunt (in press) found that survival of 1 to 3 mm S. droebachiensis in cages with potential predators was lowest (70% after 8 wk) in the juvenile conspecific (mean ± SD size: 8.8 ± 2.2 mm TD) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Small juvenile S. droebachiensis (3−6 mm test diameter [TD]) are also vulnerable to predation by rock crabs (Cancer irroratus), juvenile lobsters (Ho marus americanus), and juvenile sculpins (Myoxocephalus octodecemspinosis), which can significantly reduce the abundance of recruits in the laboratory (Scheibling & Hamm 1991). Although predation by carnivores is the most frequently cited cause of post-settlement mortality for sea urchins, omnivorous grazers have recently been recognized as a potentially important source of mortality (Jennings & Hunt 2011). A field experiment in the Bay of Fundy, Canada (Jennings & Hunt 2011), and subsequent laboratory experiment (Jennings & Hunt in press) suggested that juvenile S. droebachiensis are a source of mortality for smaller conspecifics, though it is unclear whether the mortality occurred through 'bulldozing' (inadvertent crushing), or ingestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in field experiments, early post‐settlement sea stars and sea urchins survived better when the suite of small animals had been removed from the substrate (Keesing & Halford ; Keesing et al . ; Jennings & Hunt , ). Keesing & Halford () and Keesing et al .…”
Section: Introductionmentioning
confidence: 99%